Pembuatan Peta Administrasi Sebagai Pendukung Pembangunan Daerah Desa Bligo, Kecamatan Candi, Kabupaten Sidoarjo - Linda Dwi Rohmadiani; Moch Shofwan; Anak Agung Sagung Alit Widyastuty; Annisa Budhiyani Tribhuwaneswari; Siti Nuurlaily Rukmana; Suning Suning (Jurnal Pengabdian Masyarakat (abdira), 2022)
Bligo Village is a village-city in the Candi District area, because administratively it is a village but the livelihood of the majority of the population is as factory workers, so a complete village administrative boundary information map is needed in accordance with applicable standards. The purpose of community service is mapping of village administrative boundaries according to the Regulation of the Head of BIG No. 3 of 2016 as a village development guideline. The methods used include preparation, survey, preparation of administrative maps, verification of maps, printing and handing over of maps to villages. The main task of the implementing team is to facilitate and guide village officials. Community service activities produce village administration maps which include information in the form of village administrative boundaries, RW administrative boundaries, RT administrative boundaries, road networks, and waters.